The Buzzel About Kentuck : Settling the Promised Land - Friend, Craig Thompson (Book collections on Project MUSE., 1999)
Touted as an American Eden during the Colonial Period, Kentucky provides dramatic social histories of early America from its days as a Shawnee hunting ground to a prosperous agrarian society bordered by the best river traffic during the nineteenth century. Ten noted historians explore ideas ranging from frontier defenses and pioneer strategies, to economic and cultural opportunities in early cities, and the oft-overlooked experiences of minorities.